Dicer1 ablation in osterix positive bone forming cells affects cortical bone homeostasis - Bendre A; Moritz N; Väänänen V; Määttä JA (ELSEVIER SCIENCE INC, 2022)
The RNAse III enzyme Dicer plays a major role in the processing of microRNAs from large pre-miRNAs. Dicer1 processed microRNAs are known to play a comprehensive role in osteoblast differentiation, bone remodeling and skeletal disorders. Targeted deletion of Dicer1 in osteo-progenitor cells is deleterious to fetal survival whereas targeted deletion in mature osteoblasts leads to an increase in bone mass. To address the role of Dicer1 in postnatal skeletal homeostasis, we generated a pre-osteoblast specific Dicer1 knockout model employing Tamoxifen controllable Cre allele, enabling us, via tamoxifen administration, to time-controllably ablate Dicer1 gene expression in osterix expressing bone forming cells in post-natal mice. Inactivation of Dicer1 in osterix positive bone forming cells led to striking dysregulation of cortical bone formation in pre-pubertal as well as adult mice. Cortical bone thickness was found to be significantly decreased in the Cre + femora of both young and adult mice. Further, biomechanical testing experiments showed increased ductility, reduced stiffness and altered load at upper yield among the Cre + tibiae. Our results suggest that Dicer1 processed microRNAs might play an important role in the regulation of post-natal cortical bone formation. (C) 2017 The Authors. Published by Elsevier Inc.